Design and Analysis of an Improved Nucleotide Sequences Compression Algorithm Using Look up Table (LUT) - Govind Prasad Arya; R.K. Bharti; Devendra Prasad (International Journal of Advances in Applied Sciences, 2018)
DNA (deoxyribonucleic acid), is the hereditary material in humans and almost all other organisms. Nearly every cell in a person’s body has the same DNA. The information in DNA is stored as a code made up of four chemical bases: adenine (A), guanine (G), cytosine (C), and thymine (T). With continuous technology development and growth of sequencing data, large amount of biological data is generated. This large amount of generated data causes difficulty to store, analyse and process DNA sequences. So there is a wide need of reducing the size, for this reason, DNA Compression is employed to reduce the size of DNA sequence. Therefore there is a huge need of compressing the DNA sequence. In this paper, we have proposed an efficient and fast DNA sequence compression algorithm based on differential direct coding and variable look up table (LUT).